Farmer and Extension Staff Training on Agroecological Farming Practices - Dube, Farayi; Magaisa, Alec; Moyo, Martin (International Crops Research Institute for the Semi-Arid Tropics, 2024)
This report documents the activities of a three-day farmer training program conducted in August 2024 in Hwange and Lupane districts of Zimbabwe, focusing on enhancing the adoption of agroecological farming practices among smallholder farmers. Recognizing the significant impact of climate change, soil degradation, and declining agricultural productivity on these semi-arid regions, the training aimed to: 1. Introduce the principles of agroecology 2. Provide practical demonstrations of key Integrated Soil Fertility Management (ISFM) practices including compost making and urea treatment of stover 3. Facilitate knowledge exchange and peer learning through interactive sessions and discussions among farmers and extension staff 4. Empower farmers with the knowledge and skills to adopt and adapt agroecological practices to their specific needs and conditions, ultimately enhancing agricultural productivity, improving food security, and enhancing their livelihoods